Participatory research on the political engagement of Roma in Slovakia - Hrustič, Tomáš (Romano džaniben, 2018)
The aim of this study is to assess the participatory evaluation of the program of Roma political participation of the National Democratic Institute and to reflect on selected aspects of the participatory nature of this research. At the beginning of the study I will introduce very briefly the program of Roma political participation and the process of participative evaluation with emphasis on community based participatory research. Subsequently, the study looks at some aspects of participatory research and tries to reflect on them and evaluate the potential for other similar scientific and application projects, as well as for members of the affected Roma communities and research participants.